(untitled) (Research, Society and Development, 2024)
This research aimed to present the agronomic results and the productive and technological characters of extra-long fiber of the traditional arboreous cotton, variety Veludo C-71 (Bulk), aiming to encourage and expand its cultivation in the Brazilian Semiarid. As it is a job and income proposal for the Northeast region, Embrapa Algodão (Cotton) has identified important technological processes related to the production system that enhance the yield and improve the quality of the cotton Gossypium hirsutum, marie galante breed, whose fiber over 36 mm in length manages to reach the highest market price. The study is based on a narrative review of the arboreal cotton plant (Bulk Veludo C-71). Based on the results obtained (explored in two cultivation cycles in the same year) for Bulk Veludo C-71 in rainfed conditions supplemented with irrigation, it is expected to reach a production between 800 to 1,000 Kg/ha/year of cotton in seed, combined with adequate soil preparation and efficient cultural management. In addition, producers should prefer to grow extra cotton long-fiber cotton (tope line material) than another variety of intermediate fiber quality.